L’emploi de modèles intersectoriels rectangulaires à coefficients modifiables pour simuler la propagation de la demande pour les fins de la planification du développement industriel - Bergeron, I.; Matuszewski, T. (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
This article presents a methodology which draws heavily on the philosophy of the Input-Output models and having been made completely operational has already been used on three occasions in two countries for the purposes of regional development of construction materials industries.This methodology, or more precisely the strictly formalized part of it is an extension of that of rectangular Input-Output models with modifiable coefficients. Thus, not surprisingly, it resembles fairly closely the approach by simulation, although the proposed model contains some simple optimizing sub-models. While obviously normative, these sub-models play a descriptive rôle in the model as a whole.It is to be noted that the approach presented here can be applied to only one sector of the economy at a time. What is more, although capable of various extensions it will never be more than an auxiliary instrument destined to be used jointly with other analysis and planning instruments.It is vital for any valid regional analysis not to restrict its investigations exclusively to what goes on in the region directly concerned. Even if the objective of the analysis is limited to a single region, one must take into account the interrelations between regions within the national economy and with foreign economies: important feedbacks affecting the region concerned may on occasion travel far beyond its limits before returning. The type of a model presented here, thanks to a great number of interrelations of which it can systematically keep track may turn out to be particularly useful here.